Volume Tables for Pinus kesiya - Jain, R. C.; Bhattacharya, P. K.; Rawat, J. K. (Indian Forester, 1989)
Volume Tables for Pinus kesiya were prepared by using data from Orissa, U.P., West Bengal and Tamil Nadu. The best fit was obtained by using the model V=a + bD2H for general volume tables. Local volume tables were also prepared for Koraput and Balliguda Divisions of Orissa State separately as the sites were found to be significantly different. The model âˆš V =a+bD was found most appropriate for preparing local volume tables.